Role of Ramadan Fasting on Secretory IgA and Statherin Levels in Individuals with Dental Caries - Mohammad, Baraa S.; Taha, Ghada I. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Tooth decay happens when bacteria in the mouth create acid from carbohydrates that can be fermented. Along with factors related to the person (like genetics or oral hygiene habits) and saliva, this process leads to cavities. During Ramadan fasting, when eating habits change, there could be effects on health, particularly on the salivary biomarkers that are important for dental well-being. Objectives: This cross-sectional study aimed to detect the activity and concentrations of salivary levels of secretory immunoglobulin A and Statherin during and after Ramadan fasting and to evaluate the association between these biomarkers with dental caries. Methods: The study comprised 40 individuals, aged 20-25 years, diagnosed with dental caries. Participants were assessed for periodontal parameters using the Plaque Index and the Gingival Index. Saliva samples were collected during the fourth week of Ramadan fasting and two weeks after Ramadan fasting. The concentrations of both secretory IgA and Statherin were measured in salivary samples using Enzyme-Linked Immunosorbent Assay . Results: A significant decrease in the mean concentration of secretory immunoglobulin A was observed during Ramadan fasting (2.14±0.21 ng/L) compared to post-fasting (3.34±0.35 ng/L) (p=0.001). However, there was a non-significant difference (p=0.05) in statherin levels between the fasting state (2.25±0.18 ng/L) and the post-fasting state (2.85±0.22 ng/L). No statistically significant difference was found concerning both the Plaque Index and the Gingival Index within fasting and post-fasting state. Conclusion: Low concentration of sIgA and Statherin during Ramadan fasting may indicate altered salivary gland activity or systemic response to fasting, potentially affecting oral health.